Does serum neurofilament light help predict accelerated cognitive ageing in unimpaired older adults? - Collins, Jessica M.; Bindoff, Aidan D.; Roccati, Eddy; Alty, Jane E.; Vickers, James C.; King, Anna E. (Frontiers in Neuroscience, 2023)
Neurofilament light (NfL) is a blood biomarker of neurodegeneration. While serum NfL levels have been demonstrated to increase with normal ageing, the relationship between serum NfL levels and normal age-related changes in cognitive functions is less well understood. The current study investigated whether cross-sectional serum NfL levels measured by single molecule array technology (Simoa) mediated the effect of age on cognition, measured by a battery of neuropsychological tests administered biannually for 8 years, in a cohort of 174 unimpaired older adults (50 years) from the Tasmanian Healthy Brain Project. Mediation analysis was conducted using latent variables representing cognitive test performance on three cognitive domains -episodic memory, executive function, and language (vocabulary, comprehension, naming). Cognitive test scores for the three domains were estimated for each participant, coincident with blood collection in 2018 using linear Bayesian hierarchical models. Higher serum NfL levels were significantly positively associated with age (p < 0.001 for all domains). Cognitive test scores were significantly negatively associated with 2This is a provisional file, not the final typeset article age across the domains of executive function (p < 0.001), episodic memory (p < 0.001) and language (p < 0.05). However, serum NfL levels did not significantly mediate the relationship between age and cognitive test scores across any of the domains. This study adds to the literature on the relationship between serum NfL levels and cognition in unimpaired older adults and suggests that serum NfL is not a pre-clinical biomarker of ensuing cognitive decline in unimpaired older adults.